2010
DOI: 10.1590/s0080-62342010000200019
|View full text |Cite
|
Sign up to set email alerts
|

Saúde mental e enfermagem na estratégia saúde da família: como estão atuando os enfermeiros?

Abstract: O elo entre as práticas de saúde mental e a Estratégia Saúde da Família está alicerçado no vínculo, na corresponsabilidade, no envolvimento e conhecimento do grupo familiar. Estudo do tipo analítico, com abordagem qualitativa, utilizando a técnica de história oral temática. Foi realizado com dez enfermeiros pertencentes a três unidades de saúde da família do Distrito Sanitário Oeste da cidade de Natal/RN. Seu objetivo foi descrever as atividades voltadas para a atenção ao portador de transtorno mental na Estra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
35

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 6 publications
(9 reference statements)
1
2
0
35
Order By: Relevance
“…(8) Men were more prevalent them women, which can be explained by the fact that the psychoactive substance dependence is more prevalent among men, moreover, in general, women seek health services for treating addiction much less than men. (9,10) These data, as the mean age of men users (20-59 years) were found in other studies. (6,7) They are under economic activity, which generates negative impact on the city's economy.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…(8) Men were more prevalent them women, which can be explained by the fact that the psychoactive substance dependence is more prevalent among men, moreover, in general, women seek health services for treating addiction much less than men. (9,10) These data, as the mean age of men users (20-59 years) were found in other studies. (6,7) They are under economic activity, which generates negative impact on the city's economy.…”
Section: Discussionsupporting
confidence: 82%
“…This finding was corroborated by a study, which showed that drug therapy in mental service users, as well as its prescription and dispensation are disjointed among the professional team, occurring sometimes indiscriminate, random and non-orientation prescription for user and family. (9) Consequently, the authors listed abusive use, dependence, interruption and interaction with other substances, which offers potential risk to users. Other authors confirm the data about the indiscriminate use of psychoactive drugs without psychiatric and/ or psychological follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Tais mudanças envolvem, sobretudo, reorientação e reformulação dos modelos assistenciais que passam a ser orientados para a atenção comunitária, considerando a família, o meio onde está inserido o usuário, o vínculo e a corresponsabilização entre profissionais e sujeitos no desenvolvimento do cuidado, o que transpõe o modelo hospitalocêntrico até então vigente (12)(13) .…”
Section: Resultsunclassified
“…Porém, é possível, na ESF, atender grande parcela dessa população, com intervenções precoces, visando a prevenção e a educação em saúde, abordagem multidisciplinar cujo objetivo é o cuidado integral em saúde, com o comprometimento profissional relativo às ações a serem desenvolvidas (15) . Infere-se que os entrevistados percebem a importância do seu trabalho junto à pessoa com transtorno mental e sua família, porém, admitem a sua pouca capacitação para o cuidado em saúde mental.…”
Section: A Escassez De Educação Continuada Em Saúde Mental Como Obstáunclassified